ISLAMIC HIGHER EDUCATION QUALITY PLANNING: IMPLEMENTATION OF DEMING’S PRINCIPLES THROUGH THE INTERNAL QUALITY ASSURANCE SYSTEM - Alifia Taufika Rahmah; R. Madhakomala (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2025)
This study analyzes the implementation of the System of Internal Quality Assurance (SIQA) in planning the Internal Quality Assurance System of Higher Education (SPMI-PT) based on W. Edwards Deming's 14 Principles at UIN Syarif Hidayatullah Jakarta. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis of curriculum, human resources, facilities, learning processes, and budgeting. Findings indicate that SIQA strengthens institutional quality culture and academic planning by integrating curriculum data, monitoring learning, and digitizing quality documentation. Deming’s principles are evident in constancy of purpose through Graduate Learning Outcomes (GLOs) and continuous improvement via semester-based evaluation cycles. While transparent assessments help drive out fear, increased administrative workloads remain a challenge for lecturers. SIQA-supported data integration further enhances evidence-based decision-making in budgeting and performance evaluations. Ultimately, SIQA acts as a catalyst, transforming quality planning from a manual, reactive process into a proactive, digital system. This study contributes empirically to applying Deming's principles within digital-based quality assurance in higher education.